2020
DOI: 10.21203/rs.2.20792/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The dose - response association between fluid overload and hospital mortality in critically ill patients: a multicenter, prospective, observational cohort study

Abstract: Background Fluid management is important for ensuring hemodynamic stability in critically ill patients but easily leads to fluid overload. However, the optimal fluid balance plot or range for critically ill patients is unknown. This study aimed to explore the dose-response relationship between fluid overload (FO) and hospital mortality in critically ill patients.Methods Data were derived from the China Critical Care Sepsis Trial (CCCST). Patients with sequential fluid data for the first 3 days of admission to … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…One must also consider that there is an accompanying sodium load as albumin formulations typically have a sodium concentration similar to that of normal saline (as detailed in Table 2). This is a particularly relevant concern given that worse outcomes are found in both critically ill patients and patients on maintenance HD with more fluid overload (29)(30)(31)(32). The basis for intravenous albumin use in the setting of KRT (including maintenance HD) is generally extrapolated from the results of studies in critical care but, as further discussed below, is not backed by high-quality trials designed specifically to assess its effect on KRT-related outcomes.…”
Section: Albumin Usage For Intradialytic Hypotensionmentioning
confidence: 99%
“…One must also consider that there is an accompanying sodium load as albumin formulations typically have a sodium concentration similar to that of normal saline (as detailed in Table 2). This is a particularly relevant concern given that worse outcomes are found in both critically ill patients and patients on maintenance HD with more fluid overload (29)(30)(31)(32). The basis for intravenous albumin use in the setting of KRT (including maintenance HD) is generally extrapolated from the results of studies in critical care but, as further discussed below, is not backed by high-quality trials designed specifically to assess its effect on KRT-related outcomes.…”
Section: Albumin Usage For Intradialytic Hypotensionmentioning
confidence: 99%
“…A higher cumulative uid balance was an important factor associated with 28-day mortality following AKI. 22 In support of a conservative approach, the results of the pilot Conservative Versus Liberal Approach to Fluid Therapy of Septic Shock in Intensive Care (CLASSIC) trial showed that AKI occurred less often in patients with septic shock who were randomly assigned to a restrictive uid strategy. 23 Our results showed that uid strategy did not affect mortality nor length of ICU stay.…”
Section: Discussionmentioning
confidence: 99%
“…shown that positive cumulative fluid balance is associated with mortality and other poor outcomes, especially in patients with AKI [28,29].…”
Section: Real-world Use Of [Timp-2]*[igfbp7]mentioning
confidence: 99%